Prevalence and Progression of Cognitive Impairment in Atrial Fibrillation Patients after Treatment with Catheter Ablation or Drug Therapy - Tina S. Tischer; Daniel Nitschke; Isabelle Krause; Günther Kundt; Alper Öner; Giuseppe D’Ancona; Erdal Şafak; Hüseyin Ince; Jasmin Ortak; Evren Caglayan (Cardiology Research and Practice)
Purpose. In atrial fibrillation (AF) patients, the effect of catheter ablation or drug therapy on cognition is currently not well investigated. Therefore, we prospectively evaluated AF patients who were either treated 'with drug therapy or underwent catheter ablation for the prevalence and progression of cognitive impairment (CI). Methods. Randomized participants of the CABANA trial (catheter ablation versus antiarrhythmic drug therapy for atrial fibrillation) and the CASTLE-AF (catheter ablation versus standard conventional treatment in patients with left ventricular dysfunction and atrial fibrillation) study were assessed twice within 6 months by Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) in our institution. Results. Forty-five patients from both trials were investigated, and twenty-eight patients received catheter ablation, whereas seventeen patients received drug therapy for rhythm or rate control. The mean age of the twenty-one CABANA trial patients (AF group) was 68.8 ± 7.0 years and of the twenty-four CASTLE-AF study patients (AF/HF group) was 66.8 ± 8.1 years, respectively. Mean time from ablation/randomization to the first interview was 16.8 ± 11 months in the AF group and 28.3 ± 18.4 months in the AF/HF group, respectively. All patients investigated were classified as cognitively impaired with mean cutoff scores <24 by MoCA. Overall, we could not detect significant differences in medically treated versus catheter ablation patients within both groups in mean MMSE or MoCA scores between the first and the second interview (p>0.09). Moreover, patients who received catheter ablation did not show statistically significant differences in the prevalence or progression of cognitive impairment compared to patients who were treated medically, neither within the two groups nor between AF and AF/HF patients (p>0.05). Conclusions. Prevalence of cognitive impairment in AF patients with comorbidities is substantial. However, in this preliminary prospective study, no apparent impact of AF pretreatment on the prevalence and course of cognitive impairment could be observed.